(untitled) (Research, Society and Development, 2021)
Cryptosporidium spp. are opportunistic parasites with zoonotic potential transmitted by ingestion of contaminated water and food, the infection consists of severe diarrhea leading to the death of babies and immunocompromised individuals. In the veterinary, it can generate economic losses due to the death of calves, these animals being a possible source of transmission of the parasite. Nitazoxanide and halofuginone are the only drugs approved for treatment in humans and calves respectively, however there are restrictions on their use. There is still no vaccine against cryptosporidiosis in humans or animals and its development is a great challenge. Our objective with the present work was to write a systematic review of the literature addressing the progress of studies on vaccines against cryptosporidiosis. The recommended guidelines for RSL were used, with the aid of the StArt software (State of the Art through Systematic Rewiews). The research took place in the databases: Lilacs, PubMed, Scielo, Science Direct, Scopus, Embase and Medline. In 30% of the selected articles, the calves were the study animal and in 50% the mice; 40% of the studies were with vaccines derived from recombinant proteins and 30% of the research was aimed at inhibiting the parasite from entering cells and activating the host’s protective immunity. So far, a vaccine with no proven efficacy or an ideal cost-benefit has been developed. Many candidate antigenic targets for a vaccine have been characterized, in addition to elucidating the immunogenicity mechanism of Cryptosporidium spp. in the infected individual. However, another antigenic targets for a vaccine can be searched in future studies.